(untitled) (Global Journal of Computer Science and Technology, 2013)
A model clone is a set of similar or identical fragments in a model of the system Understanding and Identifying model clones are important aspects in software evolution During the Evolution of the Software product Cloning is often a strategic means for the same Clone detection techniques play an important role in software evolution research where attributes of the same code entity are observed over multiple versions To successfully create any method or technique for model clones detection we will have to study all the models defined in UML including internal and External Structure of UML This paper reviews some of the techniques available for the Model Clone Prevention and Detection